Effectiveness Of Waste Banks In Increasing Income For Contractual Employees (Case Study: Green Hd Waste Bank In Bengkulu City) - Levy Oktridarti; Imron Rosyadi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study examines the effectiveness of Green HD Waste Bank in increasing the income of contractual employees in the RSHD area of Bengkulu City. Green HD Waste Bank was initially established to support environmental sustainability by encouraging waste separation and recycling within the community. Over time, it has also proven to offer economic benefits, particularly for contractual staff at RSHD Bengkulu City who participate as members or clients of the waste bank. Using a qualitative research approach, this study conducted in-depth interviews with the waste bank's manager, employees, and clients to understand the dual role of Green HD Waste Bank in environmental preservation and income enhancement. Findings indicate that Green HD Waste Bank not only effectively contributes to a cleaner and more sustainable environment but also provides supplemental income, thus enhancing the financial well-being of contractual employees involved in the program.